Pengaruh Variasi Roller Standar Dengan Roller Racing Terhadap Performa Honda Beat 110 Pgm-Fi Tahun 2015 - Tegar Windriawan, Taufik; Oktaviano, Rizal; Roif Fadlan, Mokhamad; Cahyono, Setiyo; Jaya Saputra, Trisma (Jurnal Etnik: Ekonomi-Teknik, 2023)
The automotive industry is experiencing a very rapid development of science and technology. CVT (Continously Variable Transmission) is a transmission that is able to change the effective gear ratio smoothly or without pause so it is often called a gearless transmission. The compressive force of the centrifugal roller is influenced by the weight of the roller and the rotation of the engine itself, the heavier the roller, the greater the force to push the movable drive face on the drive pulley which results in a smaller pulley diameter. The purpose of this study is to determine the difference in power and torque generated from the comparison of the weight of standard rollers with racing rollers on a 2015 Honda Beat PGM-Fi motorcycle. In this study using a variation of standard ballast type and 11 gram racing ballast type. The research was conducted by experimental method or testing with the help of dyno tools. The results of research on the effect of the weight of standard rollers and racing rollers that produce maximum power at 6000 rpm with a power of 7.22 Hp using an 11 gram roller (racing). On a 13 gram roller (standard) the maximum power is generated at 7000 rpm with a power of 6.68 Hp. The torque produced on the 13 gram roller (standard) produces maximum torque at 6000 rpm with a torque result of 7.94 Nm. While the 11 gram roller (racing) also produces maximum torque at 6000 rpm with a torque of 8.57 Nm. By replacing the 13 gram roller weight (standard) with a lighter roller weight or 11 gram roller (racing) affects the power and torque of the 2015 Honda Beat Pgm-Fi motorcycle. The power and torque of the motorcycle are much better and more dominating by using a roller weight of 11 grams (racing).